Simplification of Complex WWTP Models into Simple Design and Evaluative WRRF Tool - Nsengiyumva, Olivier (Department of Civil Engineering, 2021)
Wastewater treatment plant (WWTP) steady-state models have been used, historically, by consulting engineers and researchers for design, process optimisation, and to study and evaluate various operating scenarios. These models have, however, been generally developed for single unit process which limits their use. In addition, there have been three recent shifts in the past two decades from conventional design and modelling of WWTPs. Firstly, the shift from single unit to plant-wide modelling. Secondly, WWTPs are considered as water and resource recovery facilities (WRRFs). Lastly, there has been a growing interest to use the developed plant-wide steady-state models by stakeholders i.e., plant operators, designers and decision-makers who have limited technical expertise in WWTP modelling. These stakeholders use these models for design, evaluation and optimisation of scenarios. The later shift has raised the debate of complexity versus simplicity of the developed steady-state models. In addition to the aforementioned shifts, there has been limited research on the impact of sludge return liquors on the overall plant performance especially in the context of South African WWTPs. Wastewater treatment plants treat influent wastewater to a specified effluent quality, through several processes, before discharging it into the receiving water bodies. One of the by-products of these treatment processes is a nitrogen (N) and phosphorus (P) rich dewatering liquor (DWL). Generally, South African WWTPs recycle the DWL to the mainstream treatment process without first undergoing any side-stream treatment process (SSTP). The recycling of such N and P rich DWLs to the mainstream process, without first going through any SSTP and/or addition of organics to the mainstream process (organics have a role to play in nutrient removal, through the provision of substrate for biomass growth and provision of electron donors in the process of denitrification) poses a problem to the treatment process. Consequently, the reactor is overloaded with nutrients without sufficient organics to remove them; hence, the plant produces poor effluent quality i.e., high N and P concentrations at high operational cost. A simplified full-scale steady-state WWTP simulation tool, namely, plant performance evaluation tool (PPET), with a user-friendly interface was developed, based on principles of sound mass balance and kinetic and stoichiometric relations over the full-scale plant, to bridge the gap between the complexity of WWTP models and the lack of technical expertise of the stakeholders. This simulation tool analyses the impact of recycling sludge dewatering liquors on the overall plant performance. Furthermore, it gives the user a platform to analyse different scenarios and provides uncompromised results that enable the user to make better design and operation decisions. The bio-augmentation batch enhanced (BABE) and struvite precipitation SSTPs, and plant performance indices i.e., effluent quality and operational cost indices, EQI and OCI, respectively, were incorporated into PPET to analyse case studies on South African plants. It was found that there are added benefits of using a SSTPs to mitigate the detrimental impacts of recycled DWL when the capacity of the plant has been exceeded. However, both BABE and struvite precipitation processes achieve different results based on the composition of the DWL that is being treated i.e., for DWL from an anaerobic digester treating waste activated sludge that is not P rich (with low EBPR), then the recommended SSTP operation would be BABE process rather than struvite precipitation. Due to the different treatment systems (i.e., with variations in influent loads, system configurations and priority end products required - energy, water, phosphorus, etc.), further investigations are required on strategies for implementation of the various SSTPs.